PENGEMBANGAN GEL EKSTRAK ETANOL CABAI RAWIT (Capsicum frutescence L) - A. Hasrawati; Aztriana Aztriana (As-Syifaa Jurnal Farmasi, 2016)
Chili Pepper (Capsicum frutescence L) is a plant that can be used for the treatment of rheumatoid arthritis (RA). Chemical constituents contained in chili pepper is capsaicin, it was stimulate the nerves that can relieve pain. The purpose of this study was to determine the gel formulation of the ethanol extract of cayenne pepper which has optimal stability by using a variation of the base. In this study, the ethanol extract of cayenne pepper (2.5%) was made using synthetic gel base (carbopol) and semisynthetic gel base (sodium carboxymethylcellulose). Evaluation  of the physical stability was tested  using stress conditions method. The stability parameters were  determined by organoleptic, viscosity and flow type. The ethanol extract of chili pepper was successfully created  gel form by using 5% of sodium carboxymethylcellulose and 1% of carbopol as a gelling agent. There was no significant change of two formulas  in  stability  evaluation  before and after  of the storage condition.